Comparison of Inhibition in Two Timed Reaction Tasks: The Color and Emotion Stroop Tasks. - Cothran, D. Lisa; Larsen, Randy (Journal of Psychology, 2008)
The authors examined the cross-task consistency of the ability to inhibit the processing of irrelevant information. They compared interference scores on 2 widely used inhibition tasks and found that color word Stroop interference scores correlated with emotion word Stroop interference scores. An examination of physiological reactivity showed that, in general, the color Stroop was more arousing than was the emotion Stroop, most likely due to increased response conflict. Reprinted by permission of the publisher.